Women's authorship and editorship in Victorian culture sensational strategies - Palmer, Beth, 1982- (Oxford : Oxford University Press, 2011)
Examining the ways in which women writers used the powerful positions of author and editor to perform conventions of gender and genre in the Victorian period, this book considers the work of Mary Elizabeth Braddon, Ellen Wood and Florence Marryat to explore their mutually-influential strategies of authorship and editorship.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: English fiction -- 19th century -- History and criticism; English fiction -- Women authors -- History and criticism; Periodicals -- Publishing -- Great Britain -- History -- 19th century; Women and literature -- Great Britain -- History -- 19th century; Braddon, M. E. -- 1835-1915 -- Criticism and interpretation; Wood, Henry, -- Mrs., -- 1814-1887 -- Criticism and interpretation; Marryat, Florence, -- 1837-1899 -- Criticism and interpretation